2010
DOI: 10.1371/journal.pone.0012562
|View full text |Cite
|
Sign up to set email alerts
|

Influenza A (H1N1) 2009 Antibodies in Residents of New South Wales, Australia, after the First Pandemic Wave in the 2009 Southern Hemisphere Winter

Abstract: BackgroundThe first wave of pandemic influenza A(H1N1)2009 (pH1N1) reached New South Wales (NSW), Australia in May 2009, and led to high rates of influenza-related hospital admission of infants and young to middle-aged adults, but no increase in influenza-related or all-cause mortality.Methodology/Principal FindingsTo assess the population rate of pH1N1 infection in NSW residents, pH1N1-specific haemagglutination inhibition (HI) antibody prevalence was measured in specimens collected opportunistically before (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
83
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(100 citation statements)
references
References 20 publications
15
83
2
Order By: Relevance
“…Most of the results discussed earlier correlate well with previous publications describing the dynamics of the pandemic virus infections in different countries and age distribution 1, 11, 18, 19, 20, 21, 22…”
Section: Discussionsupporting
confidence: 89%
“…Most of the results discussed earlier correlate well with previous publications describing the dynamics of the pandemic virus infections in different countries and age distribution 1, 11, 18, 19, 20, 21, 22…”
Section: Discussionsupporting
confidence: 89%
“…In the United Kingdom, about 20% of the over-65-year-olds had cross-reactive antibodies against the 2009 virus before the pandemic while in the other age groups lower rates of seroprevalence were observed (16,27). Similar patterns were found in Italy (30), Taiwan (18), New Zealand (5), and Australia (26), with over 60% of samples being positive in some cohorts older than 85 years (13). In contrast, in Singapore and Hong Kong, the baseline seroprevalence in all age groups was equal to or below 5% (9,38), and in China no preexisting antibodies could be shown in rural farmers aged over 60 years (8).…”
Section: Seroprevalence Before and After The 2009 Influenza A(h1n1) Pmentioning
confidence: 62%
“…Several studies from different continents have shown high levels of cross-reactive antibodies to A(H1N1) 2009 in the serum of donors who had been exposed to the 1918 influenza virus (13,19,20), suggesting long-lasting immunologic memory of the initial influenza (11,19,39). These results could explain the reduced attack rates among older individuals during the 2009 pandemic.…”
Section: Seroprevalence Before and After The 2009 Influenza A(h1n1) Pmentioning
confidence: 98%
“…Sensitivity at the peak of the season corresponds to data from a seroprevalence survey conducted in NSW following the 2009 pandemic, which calculated the population rate of pandemic H1N1 influenza infection to be 28%. 24 However, it is known that a range of factors contribute to this result, including health-seeking behaviour, clinical testing practices and the prevalence of influenza.…”
Section: Sensitivitymentioning
confidence: 99%